Death, sex, and sugars: variations in nonstructural carbohydrate concentrations in a sexually plastic tree. Issue 2 (20th February 2020) - Blake‐Mahmud, Jennifer; Struwe, Lena
Abstract : Premise: Environmental sex determination (ESD) is a rare sex determination system in which individuals may switch sex expression throughout their lifetimes in response to environmental factors. In sexually stable species, individuals usually bear more female flowers if the plants are larger, have greater access to limiting resources, or are in better condition. Research regarding sexually plastic species with ESD and how resources correlate with sex expression is limited. Furthermore, most research investigates resources at the population level, failing to account for resources available to individuals for growth, maintenance, or reproduction. Methods: Acer pensylvanicum is a species that is known to switch sex. Using twig samples collected during 2014–2016 in December and May, we analyzed resource status in the form of stored nonstructural carbohydrates (NSCs) and compared this with expressed sex. Results: We found that females had higher sugar concentrations than males. Furthermore, males changing expression to female had higher sugar concentrations during the prior winter than did males remaining male. We found that size was not a key predictor: neither male nor female‐flowering individuals increased NSC concentrations with size. Dying female trees had high concentrations of NSCs throughout the dying process and only manifested reduced NSCs once dead. Conclusions: This is the first study showing significant correlations between NSCs and sex expression in a plant species with ESD. These findings support the hypothesis that sex switching could be a consequence of increased resource availability and that the high female mortality of A. pensylvanicum populations is likely not a direct result of carbon starvation.